Drivers of species richness and community integrity of small forest patches in an agricultural landscape. (22nd November 2018) - Takkis, Krista; Kull, Tiiu; Hallikma, Tiit; Jaksi, Piia; Kaljund, Karin; Kauer, Karin; Kull, Thea; Kurina, Olavi; Külvik, Mart; Lanno, Kaire; Leht, Malle; Liira, Jaan; et al.
Abstract: Questions: Long‐term fragmentation and land use in Europe have created a landscape pattern where small forest patches are embedded among agricultural landscapes. These small forest patches can be one of the few habitats left to maintain the species richness and ecosystem functions within intensively managed agroecosystems. We ask, which factors determine vascular plant species richness, community composition and forest community integrity in small forest patches in an agricultural landscape? Location: NE Estonia. Methods: We combine island biogeographic theory (patch area and isolation) with the properties of the surrounding landscape and local environmental conditions within a patch to study the drivers of species richness and community integrity. Results: Patch area together with local environmental factors (understorey light conditions and soil reaction) determined both species richness and community integrity. Total species richness and forest generalists were related to patch area alone, whereas forest specialists were additionally dependent on patch light conditions. Species richness of grassland specialists in the forest patches increased with the amount of natural habitat in the surrounding landscape, while the presence of synanthropic species was positively related to soil reaction. Forest community integrity was higher in larger, more shaded patches with low soil reaction, which together defined suitable conditions for forest communities and hindered the intrusion of species from other habitats. Conclusions: Under a suitable set of conditions, encompassing both favourable landscape and local environmental conditions, even small forest patches can provide habitat for both forest and grassland communities in agricultural landscapes. Comprehensive approaches, considering species composition, environment and landscape conditions simultaneously, are needed for making reliable predictions of biodiversity patterns. Abstract : Small forest patches in agricultural landscapes can harbour diverse communities and help provide ecosystem services for the whole landscape. By analyzing a wide range of patch diversity and connectivity characteristics, we found that under suitable patch configuration and favourable environmental conditions even small forest patches can provide habitat for both forest and grassland communities in agricultural landscapes.